A Causal Role of Genetically Elevated Circulating Interleukin-10 in the Development of Digestive Cancers: Evidence from Mendelian Randomization Analysis Based on 29, 307 Subjects. Issue 7 (February 2016) - Niu, Wenquan; Pang, Qing; Lin, Ting; Wang, Zhixin; Zhang, Jingyao; Tai, Minghui; Zhang, Lingqiang; Zhang, Li; Gu, Mingliang; Liu, Chang; Qu, Kai
Abstract : Abstract: Recent studies have observed a high level of circulating interleukin-10 (IL-10) in patients with digestive cancers, yet whether elevated IL-10 is causally associated with digestive cancers so far remained unresolved. We therefore meta-analyzed available observational studies with Mendelian randomization method to explore this causal association by employing IL-10 gene 3 variants (-592C>A, -819C>T, and -1082A>G) as instruments. Data were available from 52 articles encompassing 29, 307 subjects. Subgroup analysis by cancer type indicated that -1082A>G was associated with increased risk of gastric cancer (odds ratio [OR] = 1.19; 95% confidence interval [CI]: 1.05–1.35; P = 0.006), and the association was reinforced for intestinal type gastric cancer (OR = 1.26; 95%CI: 1.09–1.44; P = 0.001). By ethnicity, risk estimate for -1082G allele carriers was increased by 21% for digestive cancers in East Asians (95%CI: 1.05–1.40; P = 0.009). As for the genotype–phenotype association, carriers of -1082G allele had an overall 20.21 pg/mL higher IL-10 level than those with -1082AA genotype ( P = 0.023). In further Mendelian randomization analysis, the predicted OR for 10 pg/mL increment in IL-10 was 1.14 (95%CI: 1.01–16.99) in gastric cancer. Our findings provided evidence for a causal role of genetically elevated IL-10 in the development of gastric cancer, especially in East Asians and for intestinal type gastric cancer. Abstract : Supplemental Digital Content is available in the text